PENGARUH MODAL, TEKNOLOGI INFORMASI, DAN JAM KERJA TERHADAP PENDAPATAN UMKM SEKTOR PERDAGANGAN DI DENPASAR TIMUR - Mahayuni, Ida Ayu Asri; Widanta, Anak Agung Bagus Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.10.TAHUN.2021DO - 10.24843/EEB.2021.v10.i10.p01, 2021)
Capital is one of the factors that has an important role in the production process, because it is needed when an entrepreneur wants to establish a new company or to expand an existing business. Information technology can be maximally utilized to accelerate productivity in a business. With this tool, it is very easy for MSME actors to increase productivity which will ultimately affect income levels. The longer the working hours of a trader to run his business, the more customers he has. The increase in the number of customers, both those who shop directly at the store or who shop via online media, is one of the factors that can affect the income earned. This study aims to determine the simultaneous and partial effect of capital, information technology, and working hours on the income of SMEs in the trading sector in East Denpasar District by using a non-probability sampling technique, namely purposive sampling using the Slovin formula so that obtained as many as 93 samples. The results showed that simultaneously all independent variables have a significant effect on the dependent variable. Partially the variables of capital, information technology, and working hours have a positive and significant effect on the income of MSME players in the trading sector in East Denpasar District.